Is the following series convergent or divergent?

$$\displaystyle{ \sum_{n=1}^{\infty} \sum_{m=1}^{\infty} \frac{\sin(n-m)}{n^2+m^2}}$$

Even if it converge I do not know to prove it. However, for example, I know that $$\sum_n \frac{\sin n}{n}$$ converges. Then, why should not converge also this double series?

Thanks in advance.

  • $\begingroup$ This question's brother remains without an answer $\endgroup$ – Elaqqad May 1 '15 at 18:52
  • $\begingroup$ if the limit exists then it's $0$ (switch $n$ and $m$) which is the case using numerical results $\endgroup$ – Elaqqad May 1 '15 at 18:58

For fixed n, let $S(m,n) = \sum_{k=1}^{m}\sin (n-k).$ Then there exists $M$ such that $|S(m,n)|\le M$ for all $m,n.$ Summing by parts for fixed $n$ we find

$$\sum_{m=1}^{\infty}\frac{\sin(n-m)}{m^2+n^2} = \sum_{m=1}^{\infty}S_m[\frac{1}{m^2+n^2}- \frac{1}{(m+1)^2+n^2}]= \sum_{m=1}^{\infty}S_m\frac{2m+1}{(m^2+n^2)((m+1)^2 + n^2)}.$$

Slap absolute values everywhere in this last sum to see its absolute value is less than

$$M\sum_{m=1}^{\infty}\frac{3m}{(m^2+n^2)^2} =\frac{1}{n^2}\sum_{m=1}^{\infty}\frac{m/n}{((m/n)^2 + 1)^2}\frac{1}{n}.$$

As $n\to \infty,$ the last sum on $m$ tends to

$$\int_0^\infty \frac{x}{(x^2+1)^2}dx < \infty.$$ It follows that there is a positive constant $C$ such that

$$\left |\sum_{m=1}^{\infty}\frac{\sin(n-m)}{m^2+n^2} \right | \le \frac{C}{n^2}$$

for all $n.$ That implies the original double sum is convergent.

  • 1
    $\begingroup$ Is $M$ depending on $n$ or not? $\endgroup$ – Elaqqad May 1 '15 at 19:35
  • $\begingroup$ It's independent of $n.$ Sum the sines as the imaginary part of a geometric sum of exponentials (the usual trick) to see this. $\endgroup$ – zhw. May 1 '15 at 19:40
  • $\begingroup$ @Elaqqad If we write $S(n,m) = \sum_{k = n-m}^{n-1} \sin k$, then multiply $\csc(1/2)\sin(1/2)$ and use the identity $\sin a \sin b = (1/2)[\cos(a-b) - \cos(a+b)]$, we obtain $$S(m,n) = (1/2)\csc(1/2)\sum_{k = n-m}^{n-1} [\cos(k - 1/2) - \cos(k + 1/2),]$$ which telescopes to $(1/2)\csc(1/2)\{\cos(n-m-1/2) - \cos(n+1/2)\}$. This is bounded by $\csc(1/2)$, so we may choose $M = \csc(1/2)$, a number independent of $m$ and $n$. $\endgroup$ – kobe May 1 '15 at 19:54
  • $\begingroup$ The $S(n,m)$ I wrote was meant to be $S(m,n)$, sorry. :) $\endgroup$ – kobe May 1 '15 at 20:01

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.